The effects of bi‐functional anti‐adhesion scaffolds on flexor tendon healing in a rabbit model. Issue 7 (9th February 2018) - Liao, Janice C. Y.; He, Min; Gan, Aaron W. T.; Wen, Feng; Tan, Lay Poh; Chong, Alphonsus K. S.
Abstract: Progressive tendon adhesion is a major challenge in flexor tendon repair. The authors developed a bifunctional anti‐adhesion scaffold and hypothesized that its application would reduce adhesion formation and deliver mesenchymal stem cells (MSCs) to enhance tendon healing. The scaffold was fabricated by an electrospinning machine before surface modification. The flexor tendons of 29 New Zealand rabbits underwent surgical repair and randomized to control, scaffold and scaffold loaded with MSC group. At 3 and 8 weeks post‐surgery, range of motion (ROM), biomechanical properties, and histology were examined. There was no significant increase in ROM and biomechanical properties between the three groups. The histology showed successful delivery of MSCs but no significant difference in nuclear morphometry. This barrier delivers and retains MSCs within the tendon repair site. However, its sheet form and wrapping around the repair site may not be optimal for tendon healing. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2605–2614, 2018.